THE ASSESSMENT OF HEALTH PROTOCOL IMPLEMENTATION IN FOOD AND BEVERAGES BUSINESS DURING COVID-19 PANDEMIC ERA - Lusi Sandra Hutahaean; Muhammad Ilyas; Marsen Isbayuputra; Ray Wagiu Basrowi; Dewi Soemarko (Universitas Airlangga, 2021)
ABSTRACTDuring the COVID-19 pandemic era, the government has implemented a new strategy of health protocol called Adaptation of New Habits to prevent COVID -19 virus spread. By implementing such protocol, it is expected that health and economic sectors can be handled well. The research aims to discover the implementation of health protocol in Indonesia’s food and beverage business, and to analyze factors that support and hamper its implementation. This research was cross-sectional research with direct observation and brief interviews with 16 food and beverage business places. Observations and interviews were guided using a checklist derived from government policies set by the ministry of health and commerce then the data will be analyzed descriptively. This research shows that the implementation health protocol remained far from expectations. Moreover, business activity, management system, and the awareness of employers, employees, as well as consumers, became a critical key in health protocol implementation. Comprehending the dangers of COVID-19 and committing to comply with health protocols are imperatives to succeed in the health protocol implementation. Keywords: Adaptation of New Habits, Health Protocol of COVID-19 Pandemic, evaluating health protocols implementation